1984
DOI: 10.1073/pnas.81.19.6009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regulation of phage lambda cII gene expression by Escherichia coli integration host factor.

Abstract: The effect of Escherichia coli integration host factor (IHF) on phage A gene expression has been examined in a simplified DNA-directed in vitro system that measures the formation of the first dipeptide of the gene product. Plasmid pKC3OcII, which contains the phage A genes N, ciH and 0, under control of the PL promoter, was used as template to study the expression of the first dipeptide of the gene products-i.e., fMet-Asp for N protein, fMet-Val for cII, and fMet-Thr for 0. Purified IHF stimulates the DNA-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…1). Consistent with this idea is the demonstration that cII synthesis in a coupled transcription-translation system is IHF dependent (this work and reference 23).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…1). Consistent with this idea is the demonstration that cII synthesis in a coupled transcription-translation system is IHF dependent (this work and reference 23).…”
supporting
confidence: 74%
“…IHF augmented the synthesis of cII mRNA; addition of IHF to clI mRNA did not increase clI translation. These authors concluded that IHF stimulates cII transcription by suppressing termination at tRl, which lies just promoter-proximal to cII (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IHF-binding sites have been identified in several bacterial (r 7~ promoter regions. These include the E. coli ilvG-MEDA operon, some bacteriophage Mu promoters, and the ~ PL and pcin promoters (Pereira et al 1988;van Rijn et al 1988;Peacock et al 1984;Griffo et al 1989). In the case of the ilvGMEDA operon, IHF binding exerts a repressive effect on the transcription of the ilvGpl pro-…”
Section: Discussionmentioning
confidence: 99%